Goodwill impairment and future cash flows under Japanese GAAP and IFRS / Shu Inoue - Shu, Inoue (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2024)
This study investigated whether the difference in the predictive value of goodwill (GW) impairment for future cash flows is caused by the discrepancies between recognition and GW amortization under the Generally Accepted Accounting Principles in Japan (J-GAAP) and the International Financial Reporting Standards (IFRS). Results showed that GW impairments reported under IFRS, which require an annual impairment test with a GW non-amortization, were more negatively related to changes in future operating cash flows than those under J-GAAP, which required a two-step impairment test with a GW amortization. Subsequent evidence suggested that the GW impairment of firms that switched their accounting standard from J-GAAP to IFRS was also negatively associated with changes in future operating cash flows. This result implies that GW impairments under IFRS are more informative and timelier than those under J-GAAP, even if shifting to IFRS is voluntary, which examines GW impairments over a long period and in a single country, allowing an examination of ignoring the difference of institutional settings across countries.